2023
DOI: 10.1007/s00401-023-02616-7
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and the pathological progression of Alzheimer’s disease are associated with low circulating choline levels

Jessica M. Judd,
Paniz Jasbi,
Wendy Winslow
et al.

Abstract: Deficiency of dietary choline, an essential nutrient, is observed worldwide, with ~ 90% of Americans being deficient. Previous work highlights a relationship between decreased choline intake and an increased risk for cognitive decline and Alzheimer’s disease (AD). The associations between blood circulating choline and the pathological progression in both mild cognitive impairment (MCI) and AD remain unknown. Here, we examined these associations in a cohort of patients with MCI with presence of either sparse or… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…However, MCS has now demonstrated structural/functional benefits in several AD-relevant models, namely Tg2576 (this report), APP/PS1 (Alldred et al 2021; Dave et al 2023), Ts65Dn (Velazquez et al 2013; Powers et al 2016; Strupp et al 2016; Powers et al 2017; Alldred et al 2021; Alldred et al 2023) and 3xTg mice (Dave et al 2023). Moreover, increasing evidence suggests that humans with AD have low serum choline and are improved by dietary choline (Dave et al 2023; Judd et al 2023a; b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, MCS has now demonstrated structural/functional benefits in several AD-relevant models, namely Tg2576 (this report), APP/PS1 (Alldred et al 2021; Dave et al 2023), Ts65Dn (Velazquez et al 2013; Powers et al 2016; Strupp et al 2016; Powers et al 2017; Alldred et al 2021; Alldred et al 2023) and 3xTg mice (Dave et al 2023). Moreover, increasing evidence suggests that humans with AD have low serum choline and are improved by dietary choline (Dave et al 2023; Judd et al 2023a; b).…”
Section: Discussionmentioning
confidence: 99%
“…In Alzheimer’s disease (AD), changes to the diet have been recommended (Bourre 2006; Power et al 2019; Mao et al 2021; Lobo et al 2022), including MCS (Strupp et al 2016; Velazquez et al 2020; Dave et al 2023; Judd et al 2023a; b). One reason for the recommendation is that serum levels of choline are low in individuals with AD (Dave et al 2023; Judd et al 2023b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Choline supplementation also reduces brain amyloid deposition in APP.PS1 AD model mice [ 10 , 16 , 17 ]. In contrast, maternal choline deficiency has negative effects on brain development, cognitive performance, and adult neurogenesis [ 18 , 19 ] and low levels of dietary choline intake are associated with AD-neuropathological progression and increased risk for dementia and AD [ 20 , 21 ]. Together, these data support the notion that adequate choline consumption may be a potential avenue for AD prevention or risk mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…More compelling results linking Alzheimer’s disease and low choline intake, on the one hand, and the neuroprotective effect of supplementing choline in AD have been reported in animal models ( Velazquez et al, 2019 , 2020 ; Wang et al, 2019 ). Furthermore, recent studies reported an association between AD progression and low circulating choline levels in humans ( Judd et al, 2023 ). In mice, dietary choline deficiency affected the function of the hippocampal network related to microtubules, regulation of the postsynaptic membrane, and the networks of proteins associated with mitochondrial function and inflammation ( Dave et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%